ANALISIS KOMPARATIF KELAYAKAN USAHA AGROINDUSTRI DODOL PADA BERBAGAI VARIAN RASA DI UD. WARNA SARI DESA SURANADI KECAMATAN NARMADA KABUPATEN LOMBOK BARAT - I NENGAH CANDRA DEWANA; MADE SUMA WEDASTRA; I GUSTI NGURAH ARYAWAN ASASANDI; I DEWA GEDE SUARTHA (GANEC SWARA, 2021)
The study, entitled comparative analysis of the feasibility of the dodol agro-industry business on various flavors at UD. Warna Sari Suranadi Village, Narmada District, West Lombok Regency, has been implemented, by purposive sampling with the consideration that at UD. Wanasari, had problems regarding business feasibility and was given permission to carry out research. The data collection techniques used were observation, interviews and documentation, while the tools used in this study were questionnaires. Then the data analysis used cost and benefit analysis, RC ratio, BC ratio and BEP      The results showed that: the dodol agro-industry which had the greatest profit and was feasible to operate per month was the jackfruit flavored dodol agro-industry, with an average profit of Rp. 3,447,500, and the acquisition of R / C = 30.45, B / C = 10.24, higher than the other variant dodol agroindustry with break-even point (BEP volume) = 121.8 mica and BEP sales value = Rp. 508,470.07. All dodol variants taste profitable and worth working on, because the RC ratio, BC ratio is> 1, so it is recommended to the owner of UD. Wanasari, Suranadi Village, Narmada District, Lombok Regency, to keep making dodol with various flavors, to attract consumers to shop at the trading business.